Developing a winning grant proposal - Orlich, Donald C.; Shrope, Nancy R. (New York : Routledge, 2013)
"In a world of tightening budgets and increased competition for grant money, Developing a Winning Grant Proposal provides the guidelines, strategies, plans, and techniques to craft a fundable grant proposal. A user-friendly, engaging, and up-to-date guide, this book covers the entire process from the inception of a good idea, to the formulation of a strong proposal, to the next steps once a proposal is funded. Providing a basic overview and helpful tools for busy faculty and researchers, this is a must-have guide for anyone interested in the mechanisms that successful grant writers employ. Special Features Include:Appendices with a "Model of a Funded Proposal" and a "Basic Toolbox for Grant Seekers"Checklists for self-evaluating the efficacy of each portion of the grant proposalCoverage of complex issues in a concise and clear manner, perfect for grant writers facing tight time constraints"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Proposal writing for grants; Fund raising; Electronic books